Assessment of cypermethrin and amitraz resistance and molecular profiling of voltage-gated sodium channel and octopamine tyramine genes of Rhipicephalus microplus - Obaid, Muhammad Kashif; Almutairi, Mashal M.; Alouffi, Abdulaziz; Safi, Sher Zaman; Tanaka, Tetsuya; Ali, Abid (Frontiers in Cellular and Infection Microbiology, 2023)
Control of ticks and tick-borne pathogens is a priority for human and animal health. Livestock-holders extensively rely on acaricide applications for tick control. Different groups of acaricides including cypermethrin and amitraz have been consistently used in Pakistan. There has been a gap in understanding the susceptibility or resistance of Rhipicephalus microplus, the most prevalent tick in Pakistan, to acaricides. The present study aimed to molecularly characterize cypermethrin and amitraz targeted genes such as voltage-gated sodium channel (VGSC) and octopamine tyramine (OCT/Tyr) of R. microplus ticks in Khyber Pakhtunkhwa (KP), Pakistan to monitor the acaricides resistance. Tick specimens were collected from cattle and buffaloes in northern (Chitral, Shangla, Swat, Dir, and Buner), central (Peshawar, Mardan, Charsadda, Swabi, and Nowshera), and southern districts (Kohat, Karak, Lakki Marwat, Tank, and Dera Ismail Khan) of KP, Pakistan. Different concentrations of commercially available cypermethrin (10%) and amitraz (12.5%) were prepared for in vitro larval immersion tests (LIT). In LIT, the average mortality rate of immersed larvae was recorded that was increased gradually with an increase in the concentration of specific acaricide. The larvae’s highest mortality rates (94.5% and 79.5%) were observed at 100-ppm of cypermethrin and amitraz, respectively. A subset of 82 R. microplus ticks was subjected to extract genomic DNA, followed by PCR to amplify partial fragments of VGSC (domain-II) and OCT/Tyr genes. The BLAST results of the consensus sequence of VGSC gene (domain-II) showed 100% identity with the acaricides susceptible tick sequence from the United States (reference sequence). Obtained identical sequences of OCT/Tyr genes showed maximum identity (94-100%) with the identical sequences reported from Australia (reference sequence), India, Brazil, Philippines, USA, South Africa, and China. Thirteen single nucleotide polymorphisms (10 synonymous and three non-synonymous) were observed at various positions of partial OCT/Tyr gene fragments. The SNP at position A-22-C (T-8-P) in OCT/Tyr gene has been linked to amitraz resistance in R. microplus ticks. Molecular analysis and LIT bioassay’s findings indicate the availability of resistant R. microplus ticks in the KP region. To our understanding, this is the first preliminary study to monitor cypermethrin and amitraz resistance via molecular profiling of cypermethrin and amitraz targeted genes (VGSC and OCT/Tyr) in combination with in vitro bioassays (LIT) in R. microplus ticks from Pakistan.